2021
DOI: 10.34172/ijhpm.2021.17
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown and Social Capital Changes Among Youths in China

Abstract: Social capital refers to the effective functioning of social groups through networks of relationships. The lockdown measures due to coronavirus disease 2019 (COVID-19) may change the social capital among youths. This study aimed to evaluate changes in social capital before and during COVID-19 lockdown among Chinese youths. It was based on the online COVID-19 Impact on Lifestyle Change Survey (COINLICS) conducted among 10 540 youths at three educational levels, including high/vocational school, undergraduate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…However, questions on each activity at three stages were placed next to each other, so their answers could reasonably be treated as good indicators for their lifestyle changes. 10 Second, variation in understanding the same questions among different individuals, especially across different educational levels, might affect the comparability of results among different educational groups. Third, the applicability of the IPAQ form to the current context need to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, questions on each activity at three stages were placed next to each other, so their answers could reasonably be treated as good indicators for their lifestyle changes. 10 Second, variation in understanding the same questions among different individuals, especially across different educational levels, might affect the comparability of results among different educational groups. Third, the applicability of the IPAQ form to the current context need to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the Second World War and the 1918 influenza pandemic, the world has not faced such unprecedented unrest like the COVID-19 pandemic due to its contagion, lack of community immunization, and uncertainty. Adolescents could be mentally sensitive to sustained stressors such as the COVID-19 pandemic [ 19 ]. A previous meta-analysis revealed that trauma exposure was significantly associated with higher odds of depression among adolescents [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have recommended that various health support materials be provided for individuals exposed to COVID-19 pandemic to potentially relieve their long-term mental health disorders that develop due to this pandemic. These include online peersupport interventions (68), cyber-counseling (69), and digital mental health services (70), which could help to detect early psychological problems and avoid mental symptom deterioration (71)(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%